2022
DOI: 10.1007/s10570-022-04450-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and modeling the hygroscopic behavior of cellulose acetate membranes

Abstract: Exploiting materials with the ability to respond to the environmental stimuli is experiencing an enormous research interest. In particular, polymers that are sensitive to the changes of humidity levels attract great attention as self-actuators. The sensitivity of these materials to the level of moisture is expressed by their hygroscopic properties, namely, the coefficient of hygroscopic expansion. In this context, this study details the effect of moisture absorption on cellulose acetate membranes, as potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It was reported that the coefficient of hygroscopic expansion of cellulose film was in the range of several tens to several hundreds of mm 3 /g. 56 4.4. Preparation of BMB Actuator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the coefficient of hygroscopic expansion of cellulose film was in the range of several tens to several hundreds of mm 3 /g. 56 4.4. Preparation of BMB Actuator.…”
Section: Discussionmentioning
confidence: 99%
“…A series of MBC bilayer films with different thicknesses of BC layer were fabricated by adjusting the volume of the BC dispersion. It was reported that the coefficient of hygroscopic expansion of cellulose film was in the range of several tens to several hundreds of mm 3 /g …”
Section: Experimental Sectionmentioning
confidence: 99%
“…c mo ref is the strain-free reference concentration. The hygroscopic swelling coefficient and saturated moisture concentration used in the model will be estimated values obtained through the calculation method presented by Khoshtinat et al [37] which defines the hygroscopic swelling coefficient as a ratio of the relative linear expansion caused by moisture absorption in a dried material to the moisture concentration at saturation as defined by the following equations:…”
Section: Numerical Simulation Modelmentioning
confidence: 99%
“…Equation (11) determines the radius of curvature as a function of the layer height ratio (m), Young's moduli ratio (n), total height (h), and misfit strain (ε misfit ) parameters (12). The radius can then be inserted into Equations (17) and (18) to determine the curvilinear position of the fluid front as a function of the wetted length, or into Equations ( 18) and (19) to determine the position of the B-MaC tip as a function of the wetted length.…”
Section: Final Combined Modelmentioning
confidence: 99%
“…Although Timoshenko’s analysis scope was limited to just metals and temperature, there have been a significant amount of simulations that show the bi-metal modeling can be applied to bilayers made of different materials and subjected to other external stimuli other than temperature. Materials such as polymers [ 7 , 8 ], hydrogels [ 9 , 10 , 11 ], and wood/fibers [ 12 , 13 ] have been extensively studied for their bending response when used in a bilayer configuration and exposed to various external stimuli such as light [ 14 ], electricity [ 15 ], pH levels [ 16 ], humidity/moisture content [ 17 , 18 , 19 , 20 ], or a combination of these factors. These studies demonstrate the potential of Timoshenko’s pioneering theory in describing the bending behavior of bilayers made of various materials subjected to various external stimuli, in addition to metallic bilayers and thermal changes.…”
Section: Introductionmentioning
confidence: 99%